The background of congenital abnormalities in general, and especial consideration of rubella (German Measles), its epidemiology, symptomatology and teratology: A review of the literature - Fasser, E. (My University, 1951)
Every morbid condition, occurring in Medicine is based fundamentally on the genetic constitution of the individual, but only diseases whloh are significantly related to hereditary factors are regarded as hereditary diseases. In the thesis presented by the writer, an attempt is made to show how the environment affects the development and expression of factors genetical in origin. The first part of this work is really only a sketchy introduction to the genetic processes involved, and is presented as a background on which to paint the picture of certain conditions regarded as slgnifioantally environmental in origin,. Hence the early chapters cannot be regarded as being vety complete or detailed, but an attempt has been made to present the basic genetic laws, and to Interpret various morbid processes in the foetus and newborn In the light of these laws. Some of these pathological conditions have only recently been understood, and a few are enumerated In the hope of producing an over-all picture. Some are touched upon as being of some practical importance either . at the present date, or possibly in the near future, This brings us to the conception of "prenatal paediatrics." There is a tendency at the present time for a closer relationship to develop between obstetrician and paediatrician Just because of the newer knowledge regarding the reciprocal relationship between maternal and foetal status. Maternal nutri- Importance* Obstetricians, today, in introducing newer and safer procedures, operations, and analgaesic methods for delivering their patients, consider more and more, the management of labour in terms of the effect upon the foetus. Psychological, as well as physiological care of the pregnant woman must be instituted beoause psychological disturbances may significantly affect the actual physiology of pregnancy and parturition. Paediatric attention, initiated early in pregnancy, is therefore not necessarily an impractical procedure. As the genetlo constitution cannot be Varied the aim of “prenatal paediatrics” must be directed towards modification of adverse environmental factors. One of the great aims of Eugenics is to prevent the action of adverse genetio factors, but the scope of eugenics at.the present time Is limited in its application. There appears to be a tendency, as the centuries roll on, for balanced genetical systems to evolve, whioh seem to be resistant to change. Whether the future use of atomic radiation, either in Peace or in War, may change this, remains to be seen. The effects of maternal rubella, as described in the second part of this work, appear to be so diverse in different instances, that the operation of co-existent genetical background factors oannot entirely be excluded. It is essential to obtain better statistical Information regarding gene frequencies. Biochemistry, physiology, and Serology should be allied to Clinical and Social Medicine In an attempt to discover v i i i . and diabetes, and also various types of defedtfe fend malformations, such as congenital morbus cordis * deaf-mutism, mental defioienoy, eto. Art Investigation of the relationship between neonatal stattie fend the development of subsequent disease patterns during later childhood, or even adulthood, will undoubtedly » prove to be of the greatest import. In this work reference has been made to the value of epidemiological Btudies as a means of uncovering mechanisms which produce congenital defects. It should be remembered that, due to differences in diet, medical care, and a thousand other factors of changed environment, maternal status today is different to what it was fifty or one hundred years ago, and any effects for good or ill on the foetal population can. be unearthed by careful, prolonged statistical study. It is obvious that the correlated efforts of many branches of Ollnlcal, Experimental and Social Medicine over long.periods, are essential to produoe useful results. For lnstanoe, mongolism occurring in two slbs may not necessarily represent an hereditary condition, as one of the cases may be incidental, or dependant on environmental factors obtaining for both affected sibs. Similarly, many of the less typloal congenital defects, which in late years have been described as appearing in children born after maternal rubella may be incidental, and either represent the risk to the foetal population at large, or may yet be the means of uncovering the operation of other environmental factors as well. Hence we see the need for a oloser follow up of all morbid or abnormal conditions during pregnancy, particularly/*«,. particularly virus infections, with complete reports on the infants subsequently born, whether normal or otherwise. This need becomes clear, when the latter part of this work is consulted. The investigations carried out on maternal rubella as an aetiological factor in the production of congenital defects is presented as a most important step in the understanding and prevention of unfortunate accidents of foetal development. The present thesis is essentially a review of the literature, but several oases are presented on account.of the paucity of reports in the xrorld literature. In this connection, the writer would like to acknowledge case histories given by Doctors D. G. Melle, 0.N..Javett, M. Chitters, W, Tope, M, Epstein and C-. Faerber all of Johannesburg, and Doctors B. Epstein, P. Oosterhagen and J. Rudolph of Pretoria. Valuable assistance and great courtesy has been offered by the Matron, St. Vinoentfs School for the Deaf, Johannesburg, Mr. Wentworth of.the National Council for the Blind, Pretoria, Dr. le Riche of the Union Health Department, Pretoria, Ma.^or Dreisenstock at Defence Headquarters, Pretoria and those most efficient librarians, Miss A.C. Dick.and Miss Krige of the Witwatersrand Medical Library. My thanks are also due to the doctors at Union Health Department, Pretoria who so graciously plaoed their excellent library material at my disposal* Last but not least, I am indebted to Mrs, T. Mellet, Miss E. Marcus and my wife for clerical assistance. X. E„ F. Pretoria, January, 1951.
THESIS Presented to THE FACULTY OF MEDICINE, University of the Witwatergrand. In Partial Fulfillment of the requirements for the Degree DOCTOR OF MEDICINE.
Keywords: Teratology; Epidemiology; Rubella